Perinatal Outcome in Assisted Reproductive Pregnancies: Comparative Analysis of Reduced versus Unreduced Gestation. (23rd November 2016) - Bhandari, Shilpa; Agrawal, Pallavi; Ganguly, Ishita; Singh, Aparna; Gupta, Nitika
Abstract : Objectives . This study aims to evaluate perinatal outcomes such as gestational age at delivery and live birth rate in singleton and twin gestation with or without fetal reduction. Method . A retrospective analysis was done on patients which were divided into reduced and unreduced groups on the basis of order of reduction of one or more fetuses between 6 and 13 weeks of gestation. Patients records were studied to note gestational age at delivery/abortion, birth weight, and neonatal outcome. Result . The cohort included a total of 292 patients: 102 singletons and 190 twins. 52 pregnancies were reduced in singleton cohort and 68 were reduced in twin cohort. No statistical difference was observed in live birth rate, gestational age at delivery, and birth weight and significant higher incidence of IUGR was observed in reduced and unreduced twin gestation. In singleton pregnancies however preterm delivery rate increased with fetal reduction. Conclusion . Although reduction does not reduce the live birth rate, it does reduce gestation age of delivery and birth weight of newborn. This effect is more apparent when multiple gestation is reduced to singleton.